2020
DOI: 10.1158/2326-6074.tumimm19-a14
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A14: Neoepitope-specific CD8+ T cells in adoptive T-cell transfer

Abstract: Adoptive T-cell therapy (ACT) relies on expansion of tumor-infiltrating lymphocytes and infusion into patients following lymphodepletion, which have yielded complete responders in up to 25% of treated patients suffering from metastatic melanoma. However, a large proportion of patients have no clinical benefit (50-60%). Previous studies have found that clinical outcome correlates with tumor mutational and putative neoantigen load. Furthermore, expression of core antigen-presentation pathways including MHC class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ACT aims to generate a robust immune-mediated antitumor response via infusion of ex vivo -manipulated T cells. Studies have suggested that clinical outcomes correlate with tumor mutational and neoantigen load ( 217 219 ). Although ALL has been described as a malignancy with low mutational load, a recent analysis reported that it is possible to obtain immunodominant neoantigens that could be used to develop neoepitope-CD8+ T cells and treat patients with ALL ( 83 , 220 ).…”
Section: Into the Frontline Of All Treatment: Targeting The Immune Cellsmentioning
confidence: 99%
“…ACT aims to generate a robust immune-mediated antitumor response via infusion of ex vivo -manipulated T cells. Studies have suggested that clinical outcomes correlate with tumor mutational and neoantigen load ( 217 219 ). Although ALL has been described as a malignancy with low mutational load, a recent analysis reported that it is possible to obtain immunodominant neoantigens that could be used to develop neoepitope-CD8+ T cells and treat patients with ALL ( 83 , 220 ).…”
Section: Into the Frontline Of All Treatment: Targeting The Immune Cellsmentioning
confidence: 99%